Extended Macroscopic Study of Dilute Gas Flow within a Microcavity. (14th December 2016) - Hssikou, Mohamed; Baliti, Jamal; Alaoui, Mohammed
Abstract : The behaviour of monatomic and dilute gas is studied in the slip and early transition regimes using the extended macroscopic theory. The gas is confined within a two-dimensional microcavity where the longitudinal sides are in the opposite motion with constant velocity ± U w . The microcavity walls are kept at the uniform and reference temperature T 0 . Thus, the gas flow is transported only by the shear stress induced by the motion of upper and lower walls. From the macroscopic point of view, the regularized 13-moment equations of Grad, R13, are solved numerically. The macroscopic gas proprieties are studied for different values of the so-called Knudsen number (Kn), which gives the gas-rarefaction degree. The results are compared with those obtained using the classical continuum theory of Navier-Stokes and Fourier (NSF).